EFFECT OF HURDLE RATE AND CONFIDENCE ON COMMITMENT ESCALATION - Kevilia Rosana; Jesica Handoko (JOURNAL OF ACCOUNTING, ENTREPRENEURSHIP AND FINANCIAL TECHNOLOGY (JAEF), 2021)
Companies make investments to benefit from existing projects. Managers are responsible for every investment decision taken, which must be correct and bring big profits to the future. They have to make the right decisions in continuing or stopping the project. However, managers sometimes make wrong decisions by continuing to continue less profitable projects, known as escalation of commitment. Escalation of commitment is the decision to continue the manager's project even though it is known to be in an unfavorable state to the maximum. This study aims to determine the effect of hurdle rates and confidence on the escalation of commitment. The study's research design used a 3x2 experiment between subjects carried out to Accounting students in WMCUS who had passed the management accounting course. The data from the experiment will be analyzed using ANOVA statistical tools. The results obtained in this study are (a) hurdle rates significantly induced escalation of commitment and (b) confidence does not affect escalation of commitment. Also, there is no interaction between hurdle rates and confidence in the escalation of commitment. It concluded that using student participants tends to escalate their commitment in believing that it will provide gain in the future. The results obtained in this study are (a) hurdle rates significantly induced escalation of commitment and (b) confidence does not affect escalation of commitment. Also, there is no interaction between hurdle rates and confidence in an escalation of commitment. It concluded that using student participants tends to escalate their commitment in believing that it will provide gain in the future. The results obtained in this study are (a) hurdle rates significantly induced escalation of commitment and (b) confidence does not affect escalation of commitment. Besides, there is no interaction between hurdle rates and confidence in an escalation of commitment. It concluded that using student participants tends to escalate their commitment in believing that it will provide gain in the future